Neodymium-iron-boron magnet containing sealing film and preparation method and application of neodymium-iron-boron magnet
By using acidic resins, titanate coupling agents, silicone composites and rare earth oxides to form a sealing film, the corrosion problem of neodymium iron boron magnets in high temperature and oxidation environments is solved, and corrosion resistance is improved. The combination force achieves safe and environmentally friendly wear resistance and corrosion resistance improvement.
Patent Information
- Application Number
- CN202411264977.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-01-03
AI Technical Summary
Existing neodymium iron boron magnets are prone to corrosion in high temperature and oxidation environments, and the corrosion resistance and binding force of the galvanizing and spraying processes are insufficient, resulting in high unqualified product rates.
Using a sealing agent containing acid resin, titanate coupling agent, silicone composite and rare earth oxide, chemical bonds are formed with Ti-O-Si, Ti-O-Zn, Ti -The sealed film with molecular structure mainly composed of O-Fe, Si-O-Zn, and Si-O-Fe to improve wear resistance and corrosion resistance.
It significantly improves the temperature resistance, wear resistance and corrosion resistance of neodymium iron boron magnets, forms a transparent and bright film layer, reduces the unqualified product rate, and the sealing agent is an aqueous system, which is safe and environmentally friendly.
Smart Images

Figure CN119252636A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of surface protection of NdFeB magnets, and relates to a NdFeB magnet containing a closed film, a preparation method and an application thereof. Background Art
[0002] Sintered NdFeB magnets are widely used in various fields such as new energy vehicles, smart homes, consumer electronics and smart communications due to their excellent magnetic properties. However, sintered NdFeB magnets are an active alloy material with loose and porous materials, which are very easy to be oxidized and corroded. Therefore, in the prior art, NdFeB magnets are made to have corrosion resistance, reliable high temperature resistance and high bonding strength through electroplating and spraying processes. The common electroplating process is surface cleaning treatment + electrogalvanizing + passivation; the common spraying method is surface cleaning treatment + phosphating + spraying.
[0003] However, the existing electroplating and spraying processes still have defects. For example, when the galvanized product is heated or the equipment is inspected, the passivation film is severely worn and easily cracked, which in turn affects the corrosion resistance; the sprayed product is affected by the phosphating film bottom layer, and the PCT and bonding strength are poor, resulting in a large number of defective products.
[0004] Patent CN108221016A discloses a galvanizing sealer and a method for using the same, wherein the sealer is composed of cobalt sulfate: 0.1-10 g / L; nickel fluoride: 0.2-8 g / L; cadmium nitrate: 0.4-7 g / L; nickel sulfate: 0.3-5 g / L; sodium hypophosphite: 0.1-6 g / L; the solvent is water; after the galvanizing sealer is applied to the surface of the galvanized and passivated workpiece, the metal ions in the galvanizing sealer are reduced to metal elements by a reducing agent through high-temperature treatment, and then filled in the micropores of the passivation layer and covered on the surface of the passivation layer, but the protective film formed by the inorganic sealer is prone to cracking and has no elasticity.
[0005] Patent CN110189908A discloses a method for water-based environmentally friendly thin coating composite protection of NdFeB magnet materials, which includes degreasing, rust removal, sandblasting or sandpaper polishing of NdFeB; then, coating the NdFeB with a layer of water-based environmentally friendly primer; after curing, coating a layer of water-based environmentally friendly closed top coating to form a thin coating composite system. The primer uses 5-40 silane coupling agents and 3-10 titanate coupling agents. As part of the primer component, it needs to be sprayed twice, which consumes a lot of energy and is costly. Summary of the invention
[0006] In order to improve the above problems, the present invention provides a sealing agent, which, based on 100% by mass, includes 20-40% acidic resin, 10-20% titanate coupling agent, 0.5-1.5% organic silicon compound, 0.5-1.5% rare earth oxide, 5-15% alcohol solvent, and the balance is water.
[0007] Among the above components of the present invention, the acidic resin is used as the main film-forming substance, which can form a strong protective layer with the galvanized or iron-based surface to prevent the occurrence of air oxidation, corrosion and the like; the titanate coupling agent can undergo an ester exchange reaction with the acidic resin and a substitution reaction with the organosilicon complex (taking tetraisopropyl titanate as an example, -O-CH(CH3)2 therein forms a covalent bond with Zn or Fe in the passivation layer after hydrolysis; the isopropyl group is a long alkane group with good flexibility, and can be bent and entangled with the organic polymer to improve the impact strength of the material); the rare earth oxide is used as a catalyst to accelerate the cross-linking process of the reaction, which is beneficial to improving the hardness and wear resistance of the sealing layer.
[0008] According to an embodiment of the present invention, the acidic resin includes one or more of styrene sulfonic acid resin, acrylic resin, and vinyl resin.
[0009] According to an embodiment of the present invention, the titanate coupling agent includes one or more of tetraisopropyl titanate, methyl titanate, ethyl titanate, dioctyl carbonate, and the like.
[0010] According to an embodiment of the present invention, the organic silicon compound includes one or more of methylchlorosilane, phenylchlorosilane, vinylchlorosilane, hexamethyldisiloxane, octamethylcyclotetrasiloxane, dimethylcyclosiloxane and the like.
[0011] According to an embodiment of the present invention, the rare earth oxide includes one or more of lanthanum oxide and cerium oxide.
[0012] According to an embodiment of the present invention, the alcohol solvent includes one or more of methanol, ethanol, and isopropanol.
[0013] Exemplarily, the sealing agent is preferably composed of the following components: 30% acrylic resin, 15% tetraisopropyl titanate, 1% hexamethyldisiloxane, 1% cerium oxide, 10% ethanol, and the balance is water.
[0014] The present invention also provides a NdFeB magnet containing a sealing film, which comprises a NdFeB magnet substrate and a sealing film coated on the surface of the NdFeB magnet substrate;
[0015] The closed film is mainly composed of a molecular structure formed by Ti, Si, and O bonds, and forms a chemical bond with the interface metal;
[0016] The sealing film is obtained by coating the sealing agent on the surface of the zinc-plated NdFeB magnet substrate, and then performing sealing treatment and heating.
[0017] Alternatively, the sealing film is obtained by coating the sealing agent on the surface of the NdFeB magnet substrate, followed by sealing treatment and heating.
[0018] According to an embodiment of the present invention, the thickness of the sealing film is 10-40 nm, preferably 20-30 nm.
[0019] According to an embodiment of the present invention, the interface metal is Zn and / or Fe.
[0020] According to an embodiment of the present invention, the chemical bond is at least one of Ti-O-Si, Ti-O-Zn, Ti-O-Fe, Si-O-Zn, and Si-O-Fe.
[0021] The present invention provides a method for preparing the above-mentioned NdFeB magnet containing a closed film, wherein the method is a galvanizing method (i.e., method one) or a spraying method (method two);
[0022] The galvanizing method comprises:
[0023] (S1) surface cleaning to remove the oxide layer on the surface of the NdFeB magnet substrate;
[0024] (S2) electroplating: zinc plating the cleaned substrate surface;
[0025] (S3) passivation treatment: using a brightening liquid and a passivation liquid in sequence to passivate the product after galvanizing in step (S2);
[0026] (S4) Sealing treatment: using the above-mentioned sealing agent to seal the product after passivation in step (S3), heating, and obtaining a NdFeB magnet containing a sealing film;
[0027] The spraying method comprises:
[0028] (K1) Surface cleaning: Surface cleaning is the same as step (S1);
[0029] (K2) Sealing treatment: using the above-mentioned sealing agent to seal the product cleaned in step (K1) and heating it;
[0030] (K3) Spraying treatment: The product in step (K2) is first preheated and then air-sprayed with paint. After curing, a NdFeB magnet containing a closed film is obtained.
[0031] According to an embodiment of the present invention, step (S1) or step (K1) is specifically:
[0032] Surface cleaning treatment: The surface of the NdFeB magnet substrate is sandblasted or pickled to remove the oxide layer on the substrate surface.
[0033] According to an embodiment of the present invention, in step (S1) or step (K1), the sandblasting or pickling treatment adopts a technique known in the art to remove the oxide layer on the surface of the substrate.
[0034] According to an embodiment of the present invention, in step (S2), the galvanizing is a single-layer zinc electroplating process, or a double-layer or more zinc electroplating process. Preferably, the double-layer or more zinc electroplating process is a repeated single-layer zinc electroplating process.
[0035] According to an embodiment of the present invention, in step (S2), the electroplating process is: placing the cleaned surface of the substrate in a zinc plating solution and applying current.
[0036] According to an embodiment of the present invention, the zinc plating solution comprises: 300-400 g / L zinc sulfate hexahydrate, 20-30 g / L boric acid, and 20-30 g / L brightener. The brightener is well known in the art, and illustratively, the brightener model is SF-522.
[0037] The zinc plating solution of the present invention is sulfate instead of hydrochloride, which can prevent the chloride ions in the system from accelerating the corrosion of the NdFeB magnet.
[0038] According to an embodiment of the present invention, the cathode current density of the applied current is 0.5-2A / dm 2 , the current range is 15-35A.
[0039] According to an embodiment of the present invention, the temperature of the zinc plating solution is 10-40°C.
[0040] According to an embodiment of the present invention, the thickness of the coating after zinc plating is 5-15 μm.
[0041] According to an embodiment of the present invention, in step (S3), the product treated with the light emitting liquid is washed with water and then treated with a passivation liquid.
[0042] According to an embodiment of the present invention, in step (S3), the light emitting liquid is a 5-20 mL / L nitric acid aqueous solution.
[0043] According to an embodiment of the present invention, in step (S3), the temperature of the light emitting liquid is 10-40°C.
[0044] According to an embodiment of the present invention, in step (S3), the time for treating the light emitting liquid is 5-60 seconds.
[0045] According to an embodiment of the present invention, in step (S3), the passivation solution includes 10-20 g / L chromium nitrate, 1.5-3 g / L nitrilotriacetic acid, 2-4 g / L oxalic acid, 1.5-2 g / L cobalt sulfate, 0.4-4 g / L γ-aminopropyltriethoxysilane, and 0.5-0.8 g / L sodium tungstate.
[0046] According to an embodiment of the present invention, in step (S3), the temperature of the passivation solution is 10-40°C.
[0047] According to an embodiment of the present invention, in step (S3), the time for passivation solution treatment is 5-60s.
[0048] According to the implementation scheme of the present invention, step (S3) is specifically as follows: the workpiece after electroplating is first placed in a polishing liquid for chemical polishing, the temperature of the polishing liquid is 10-40°C, and the polishing liquid treatment time is 5-60s; then the workpiece after polishing is washed with water for 1-5min, and then placed in a passivation liquid for passivation treatment, the temperature of the passivation liquid is 10-40°C, and the passivation liquid treatment time is 5-60s.
[0049] According to an embodiment of the present invention, in step (S4), before the sealing treatment, the passivated workpiece may be cleaned for 1-5 minutes and then placed in a sealing agent for sealing treatment.
[0050] According to the embodiment of the present invention, in step (S4), during the sealing treatment, the temperature of the sealing agent is 20-40°C, the product is treated with the sealing agent for 5-60 seconds, and the concentration of the sealing agent is 8-12wt%. If the sealing agent treatment time is too long, it will easily cause flow lines, unevenness, etc. due to excessive film thickness or improper operation, thereby affecting the appearance.
[0051] According to an embodiment of the present invention, in step (S4), after the sealing treatment, the product is washed with clean water for 5-60 seconds.
[0052] According to an embodiment of the present invention, in step (S4), the heating temperature is 45-200°C, for example, 45°C, 60°C, 80°C, 100°C, 120°C, 140°C, 160°C, 180°C or 200°C, and the heating time is 10-60 min.
[0053] According to an embodiment of the present invention, in step (S4), the sealing treatment can be carried out by immersion pulling, atomic layer deposition, magnetron sputtering deposition and the like.
[0054] Preferably, the impregnation pulling method is as follows: the passivated NdFeB substrate is placed vertically in a sealant, the temperature of the sealant is 20-30°C, and the concentration is 8-12wt%. After sufficient impregnation, the substrate is pulled at a uniform speed, and after further heating treatment, a NdFeB magnet containing a sealing film is obtained. The impregnation time is 5-60s, the heating treatment temperature is 45-200°C, and the heating time is 10-60min.
[0055] According to an embodiment of the present invention, in step (K2), during the sealing treatment, the temperature of the sealing agent is 20-40° C., the product is treated with the sealing agent for 5-60 seconds, and the concentration of the sealing agent is 8-12 wt %.
[0056] According to an embodiment of the present invention, in step (K2), after the sealing treatment, the product is washed with clean water for 5-60 seconds.
[0057] According to an embodiment of the present invention, in step (K2), the heating temperature is 45-200° C., and the heating time is 10-60 min.
[0058] According to an embodiment of the present invention, in step (K3), the temperature of the preheating treatment is 60-70° C., and the time of the preheating treatment is 20-150 s.
[0059] According to an embodiment of the present invention, in step (K3), the curing temperature is 170-190° C., and the curing time is 15-25 min.
[0060] According to an embodiment of the present invention, in step (K3), the paint flow rate is 20-30 L / min, the pressure during air spraying is 0.2-0.3 MPa, and the paint viscosity is 10-12 s.
[0061] According to an embodiment of the present invention, in step (K3), the paint can be any paint known in the art.
[0062] The present invention also provides the use of the NdFeB magnet containing the sealing film in galvanizing and spraying for corrosion protection.
[0063] Beneficial effects of the present invention:
[0064] The NdFeB magnet containing a sealing film of the present invention can significantly improve the temperature resistance, wear resistance, corrosion resistance and bonding strength of the product through the sealing film.
[0065] In the sealant of the present invention, titanate coupling agent, organosilicon composite, rare earth oxide synergistically catalyze crosslinking reaction, and form covalent bonds with the surface metal Zn or Fe of the NdFeB magnet matrix, forming a molecular structure mainly composed of Ti-O-Si, Ti-O-Zn / Fe, and Si-O-Zn / Fe; wherein, titanium, as an electron acceptor, can catalyze the photosensitivity reaction in the system, inhibit the chemical reaction on the surface of the product, and enable the coating to maintain surface finish and stability under conditions such as strong sunlight and high temperature, thereby solving the problem that the zinc-plated passivated product is not heat-resistant, has heavy wear and poor corrosion resistance during AOI inspection, and also solves the problem that the NdFeB magnet containing the sealing film has poor corrosion resistance and bonding force. In addition, the sealant of the present invention is a water-based system, has good anti-corrosion performance and adhesion, does not contain harmful substances such as formaldehyde, benzene, and heavy metals, and forms a transparent and bright film layer after drying, which can be used as both a final anti-corrosion layer and an anti-corrosion bottom layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0066] Figure 1 This is a SEM image of the product surface in Example 5.
[0067] Figure 2 This is a SEM image of the product surface after the product in Example 5 was subjected to the wear resistance test.
[0068] Figure 3 This is a SEM image of the product surface after the product in Example 5 was subjected to a temperature resistance test.
[0069] Figure 4 This is a SEM image of the product surface in Comparative Example 1.
[0070] Figure 5 This is a SEM image of the product surface after the product in Example 1 was subjected to a wear resistance test.
[0071] Figure 6 This is a SEM image of the product surface after the product in Example 1 was subjected to a temperature resistance test. DETAILED DESCRIPTION
[0072] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0073] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0074] Comparative Example 1
[0075] 1) Sandblasting: The workpiece (i.e., NdFeB magnet substrate) was subjected to rolling sandblasting treatment, with glass beads as the spray material, a spray gun with an inclination angle of 45°, two spray guns, a rolling speed of 7 Hz, a sandblasting pressure of 1 bar, and a sandblasting time of 10 min; then the substrate was ultrasonically washed for 30 s, cleaned with 10 wt% citric acid for 15 s, and cleaned with pure water for 15 s to remove the oxide layer on the substrate surface.
[0076] 2) Electroplating: The workpiece subjected to sandblasting in step 1) is subjected to single-layer zinc electroplating, and the zinc plating solution contains 350 g / L zinc sulfate hexahydrate, 25 g / L boric acid, and 25 g / L brightener, and the brightener model is SF-522. The cathode current density is 0.8 A / dm2, the current range is 20 A, the plating solution temperature is 30° C., and the coating thickness is 6-15 μm.
[0077] 3) Passivation treatment, passivation treatment is performed on the workpiece that has been electroplated in step 2), and the workpiece after electroplating is placed in a polishing liquid for chemical polishing, 10 ml of nitric acid is used per liter of polishing liquid, and the polishing time is 15 seconds; then the workpiece after polishing is cleaned for 1 minute, and then placed in a passivation treatment liquid for passivation treatment, the passivation liquid contains 15g / L chromium nitrate, 2g / L nitrilotriacetic acid, 3g / L oxalic acid, 1.7g / L cobalt sulfate, 2g / L γ-aminopropyltriethoxysilane, and 0.6g / L sodium tungstate; the passivation liquid treatment temperature is 25°C, the time is 45s, and then washed with clean water for 30s, dried with a hair dryer, and then placed in an oven at 60°C for 45min.
[0078] Example 1
[0079] 1) Sandblasting: The specific process is the same as step 1) of comparative example 1.
[0080] 2) Electroplating treatment: The specific process is the same as step 2) of comparative example 1.
[0081] 3) Passivation treatment, passivating the workpiece that has been electroplated in step 2), placing the electroplated workpiece in a polishing liquid for chemical polishing, using 10 ml of nitric acid per liter of polishing liquid, and the polishing time is 15 seconds; then the polished workpiece is cleaned for 1 minute, and then placed in a passivation treatment liquid for passivation treatment, the passivation liquid contains 15 g / L chromium nitrate, 2 g / L nitrilotriacetic acid, 3 g / L oxalic acid, 1.7 g / L cobalt sulfate, 2 g / L γ-aminopropyltriethoxysilane, and 0.6 g / L sodium tungstate; the passivation liquid treatment temperature is 25°C, and the time is 45 seconds.
[0082] 4) Sealing treatment: After the workpiece that has been electroplated in step 3) is cleaned for 30 seconds, it is vertically placed in a sealant with a temperature of 25° C., a concentration of 10 wt %, and an immersion time of 40 seconds.
[0083] The sealing agent contains 30% acrylic resin, 15% tetraisopropyl titanate, 1% hexamethyldisiloxane, 1% lanthanum oxide, 10% ethanol, and the balance is deionized water.
[0084] After sufficient impregnation, the NdFeB substrate was pulled at a constant speed, washed with clean water for 30 seconds, dried with a hair dryer, and then placed in an oven at 60°C for 45 minutes to obtain a NdFeB magnet with a closed film.
[0085] Example 2
[0086] 1) Sandblasting: Same as step 1) in Example 1.
[0087] 2) Electroplating treatment: same as step 2) in Example 1.
[0088] 3) Passivation treatment: same as step 3) in Example 1.
[0089] 4) Sealing treatment: After the workpiece that has been electroplated in step 3) is cleaned for 30 seconds, it is vertically placed in a sealant with a temperature of 25° C., a concentration of 10 wt %, and an immersion time of 40 seconds.
[0090] The sealing agent contains 30% acrylic resin, 15% tetraisopropyl titanate, 1% methylchlorosilane, 1% cerium oxide, 10% ethanol, and the balance is deionized water.
[0091] After sufficient impregnation, the NdFeB substrate was pulled at a constant speed. After washing with clean water for 30 seconds, it was blown dry with a hair dryer and then placed in an oven at 60°C for 45 minutes to obtain a NdFeB magnet with a closed membrane.
[0092] Example 3
[0093] 1) Sandblasting: Same as step 1) in Example 1.
[0094] 2) Electroplating treatment: same as step 2) in Example 1.
[0095] 3) Passivation treatment: same as step 3) in Example 1.
[0096] 4) Sealing treatment: After the workpiece that has been electroplated in step 3) is cleaned for 30 seconds, it is vertically placed in a sealant with a temperature of 30° C., a concentration of 12 wt %, and an immersion time of 40 seconds.
[0097] The sealing agent contains 30% acrylic resin, 15% ethyl titanate, 1% hexamethyldisiloxane, 1% cerium oxide, 10% ethanol, and the balance is deionized water.
[0098] After sufficient impregnation, the substrate was pulled up at a constant speed. After washing with clean water for 30 seconds, it was blown dry with a hair dryer, and then placed in an oven at 60°C for 45 minutes to obtain a NdFeB magnet with a closed membrane.
[0099] Example 4
[0100] 1) Sandblasting: Same as step 1) in Example 1.
[0101] 2) Electroplating treatment: same as step 2) in Example 1.
[0102] 3) Passivation treatment: same as step 3) in Example 1.
[0103] 4) Sealing treatment: After the workpiece that has been electroplated in step 3) is cleaned for 30 seconds, it is vertically placed in a sealant with a temperature of 30° C., a concentration of 12 wt %, and an immersion time of 40 seconds.
[0104] The sealing agent contains 30% acrylic resin, 15% tetraisopropyl titanate, 1% hexamethyldisiloxane, 1% cerium oxide, 10% ethanol, and the balance is deionized water.
[0105] After sufficient impregnation, the substrate was pulled up at a constant speed. After washing with clean water for 30 seconds, it was blown dry with a hair dryer, and then placed in an oven at 60°C for 45 minutes to obtain a NdFeB magnet with a closed membrane.
[0106] Example 5
[0107] 1) Sandblasting: Same as step 1) in Example 1.
[0108] 2) Electroplating treatment: same as step 2) in Example 1.
[0109] 3) Passivation treatment: same as step 3) in Example 1.
[0110] 4) Sealing treatment: After the workpiece that has been electroplated in step 3) is cleaned for 30 seconds, it is vertically placed in a sealant with a temperature of 30° C., a concentration of 12 wt %, and an immersion time of 40 seconds.
[0111] The sealing agent contains 30% acrylic resin, 15% tetraisopropyl titanate, 1% hexamethyldisiloxane, 1% cerium oxide, 10% ethanol, and the balance is deionized water.
[0112] After sufficient impregnation, the substrate was pulled up at a constant speed. After washing with clean water for 30 seconds, it was blown dry with a hair dryer, and then placed in an oven at 150°C for 15 minutes to obtain a NdFeB magnet with a closed membrane.
[0113] Example 6
[0114] 1) Sandblasting: Same as step 1) in Example 1.
[0115] 2) Electroplating treatment: same as step 2) in Example 1.
[0116] 3) Passivation treatment: same as step 3) in Example 1.
[0117] 4) Sealing treatment: After the workpiece that has been electroplated in step 3) is cleaned for 30 seconds, it is vertically placed in a sealant with a temperature of 30° C., a concentration of 12 wt %, and an immersion time of 40 seconds.
[0118] The sealing agent contains 30% acrylic resin, 15% tetraisopropyl titanate, 1% hexamethyldisiloxane, 1% cerium oxide, 10% ethanol, and the balance is deionized water.
[0119] After being fully impregnated, the substrate was pulled up at a constant speed, washed with clean water for 30 seconds, dried with a hair dryer, and then placed in an oven at 200°C for 15 minutes to obtain a NdFeB magnet with a closed film.
[0120] The products in Examples 1-6 and Comparative Example 1 were subjected to abrasion resistance test, temperature resistance test, salt spray test and roughness test, and the specific test methods are as follows.
[0121] ① Roughness test: Using the needle tracing method, the stylus is gently scratched directly on the surface of the workpiece to measure the Ra value of the surface roughness.
[0122] ② Wear resistance test: Use HH-ADI-12H35 testing equipment, through the belt + machine feeding tray feeding method,
[0123] The camera triggers the sensor to identify, with a detection efficiency of 100-300 pieces / minute. Unqualified products in appearance, i.e. defective products with flowery, scratched, and inconsistent colors, are collected, and the product wear rate is calculated to obtain the wear resistance test pass rate (%).
[0124] ③ Neutral salt spray NSS: Use salt spray chamber test machine, the equipment reaches the technical level of GB10587 salt spray chamber,
[0125] Prepare sodium chloride aqueous solution with pH=6.5-7.2; test chamber temperature 35±2℃, pressure tank temperature 47±2
[0126] ℃, compressed air pressure 70-170KPa, sodium chloride solution concentration 50±5g / l, sedimentation rate 1.5ml / h+0.5ml / h; if rust appears during the test, it is unqualified. In the salt spray test, the time when rust appears is recorded, which is the salt spray time.
[0127] ④ Temperature resistance test: Place the products in a 200℃ oven with air atmosphere for 1 hour, and observe the degree of discoloration and oxidation of the products.
[0128] The test results are shown in Table 1 below.
[0129] Table 1
[0130]
[0131] As can be seen from Table 1, compared with Comparative Example 1, Examples 1-4 are more conducive to changing the preferred orientation of the zinc coating because cerium oxide is conducive to changing the preferred orientation of the zinc coating, hexamethylsiloxane can effectively inhibit the formation of oligomers, and tetraisopropyl titanate is more conducive to enhancing the corrosion resistance, glossiness and adhesion of the film after ester exchange and condensation reaction. Therefore, after the deployment of different components, Example 4 is determined to be the optimal component; by comparing the closed baking temperature of Examples 4-6, it can be seen that 150°C and 15min are the optimal parameters, and the corresponding film structure roughness is 60% lower than that of the normal product, the wear resistance is improved by 26%, and the salt spray performance is improved by 3.3 times, so Example 5 is the best component and process.
[0132] The surfaces of the products in Example 5 and Comparative Example 1 were subjected to SEM testing. The test results are as follows: Figure 1 and Figure 4 shown.
[0133] After the products in Example 5 and Comparative Example 1 were subjected to wear resistance tests, SEM tests were performed on their surfaces. The test results are as follows: Figure 2 and Figure 5 shown.
[0134] After the products in Example 5 and Comparative Example 1 were subjected to temperature resistance tests, SEM tests were performed on their surfaces. The test results are as follows: Figure 3 and Figure 6 shown.
[0135] from Figure 1-6 It can be seen that the temperature tolerance of Example 5 is much better than that of Comparative Example 1 (Comparative Figure 3 and Figure 6 ). When the baking temperature in the sealing process in Example 5 is 150°C, the cross-linking degree of the product is the most stable. It can be seen that the corrosion resistance, wear resistance and temperature resistance of the product of the present invention are much better than those of Comparative Example 1.
[0136] Comparative Example 2
[0137] 1) Sandblasting: Same as step 1) in Example 1.
[0138] 2) Phosphating treatment: the workpiece treated with rolling sandblasting is subjected to phosphating treatment in the phosphating solution for 8 minutes at a working temperature of 60°C; then washed with water for 1 minute, dried with a hair dryer, and dried at 100°C for 15 minutes; the phosphating solution comprises: 70 g / L zinc dihydrogen phosphate, 150 g / L phosphoric acid, 12 g / L tannic acid, 7 g / L calcium nitrate, 15 g / L ammonium molybdate, 60 g / L phytic acid, 20 g / L auxiliary film-forming agent, and the rest is water.
[0139] 3) Spraying treatment: The phosphating workpiece is sprayed. After the workpiece is placed on a plate, it is preheated at 70°C for 150s before spraying. The paint flow rate is 25L / min, the pressure during air spraying is 0.25MPa, and the paint viscosity is 11s. The paint is Nippon paint known in the art. After curing at 170°C for 15min, it is cooled to room temperature and unloaded to obtain a NdFeB magnet containing a closed film.
[0140] Example 7
[0141] 1) Sandblasting: Same as step 1) in Example 1.
[0142] 2) Sealing treatment: After cleaning the workpiece after sandblasting in step 1) for 30 seconds, vertically place it in a sealant with a temperature of 25° C., a concentration of 10 wt %, and an immersion time of 40 seconds.
[0143] The sealing agent contains 30% acrylic resin, 15% tetraisopropyl titanate, 1% hexamethyldisiloxane, 1% cerium oxide, 10% ethanol, and the balance is deionized water.
[0144] After sufficient immersion, start to pull the substrate at a constant speed. Then wash it with clean water for 30 seconds, blow it dry with a hair dryer, and then place it in an oven at 100℃ for 15 minutes;
[0145] 3) Spraying treatment: The sealed workpiece is sprayed. After the workpiece is placed on a plate, it is preheated at 70°C for 150s and then sprayed with paint. The paint flow rate is 25L / min, the pressure during air spraying is 0.25MPa, and the paint viscosity is 11s. The paint is Nippon paint known in the art. After curing at 170°C for 15min, it is cooled to room temperature and unloaded to obtain a NdFeB magnet containing a sealed film.
[0146] Example 8
[0147] 1) Sandblasting: Same as step 1) in Example 1.
[0148] 2) Sealing treatment: the difference from step 2) of Example 7 is that the drying temperature is 150°C.
[0149] 3) Spraying treatment: same as step 3) in Example 7.
[0150] Example 9
[0151] 1) Sandblasting: Same as step 1) in Example 1.
[0152] 2) Sealing treatment: the difference from step 2) of Example 7 is that the drying temperature is 200° C. 3) Spraying treatment: the same as step 3) of Example 7.
[0153] The products in Examples 7-9 and Comparative Example 2 were subjected to PCT test and binding strength test, and the specific test methods are as follows.
[0154] ① PCT test: The product is placed in a pressure cooker at a temperature of 121±2℃, a relative humidity of 100%, and a steam pressure of 0.105±0.01MPa. If cracking, bubbling, or rusting defects occur in the coating during the test, it is considered unqualified.
[0155] ②Binding strength test: Use Henkel Loctite adhesive TS805G to stick the product to the shear column to ensure the product is clean. After the adhesive is baked and cured, use an electronic universal testing machine to test and record the force value when the closed film layer is peeled off.
[0156] The test results are shown in Table 2 below.
[0157] Table 2
[0158] PCT Binding strength (MPa) Comparative Example 2 120h 22 Example 7 168h 30 Example 8 240h 45 Example 9 240h 42
[0159] It can be seen from Table 2 that, in Examples 7-9, compared with Comparative Example 2, after the phosphating film is replaced by the closed film, the titanate coupling agent, the organosilicon composite, and the rare earth oxide synergistically catalyze the cross-linking reaction and form covalent bonds with the surface metal Fe to form a molecular structure mainly composed of Ti-O-Si, Ti-O-Fe, and Si-O-Fe; the bonding force between the closed film and the substrate is greatly improved.
[0160] The above is an exemplary description of the embodiments of the present invention. However, the protection scope of the present invention is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A sealing agent, characterized in that The composition, based on 100% by mass, comprises 20-40% of acidic resin, 10-20% of titanate coupling agent, 0.5-1.5% of organic silicon compound, 0.5-1.5% of rare earth oxide, 5-15% of alcohol solvent and the balance of water.
2. The sealing agent according to claim 1, characterized in that The acidic resin includes one or more of styrene sulfonic acid resin, acrylic resin, and vinyl resin. Preferably, the titanate coupling agent includes one or more of tetraisopropyl titanate, methyl titanate, dioctyl carbonate, and ethyl titanate. Preferably, the organic silicon compound comprises one or more of methylchlorosilane, phenylchlorosilane, vinylchlorosilane, hexamethyldisiloxane, octamethylcyclotetrasiloxane, and dimethylcyclosiloxane. Preferably, the rare earth oxide includes one or more of lanthanum oxide and cerium oxide. Preferably, the alcohol solvent includes one or more of methanol, ethanol and isopropanol.
3. A NdFeB magnet containing a closed film, characterized in that: It includes a NdFeB magnet matrix and a sealing film coated on the surface of the NdFeB magnet matrix; The closed film is mainly composed of a molecular structure formed by Ti, Si, and O bonds, and forms a chemical bond with the interface metal; The sealing film is obtained by coating the sealing agent according to claim 1 or 2 on the surface of the zinc-plated NdFeB magnet substrate, and then performing sealing treatment and heating; Alternatively, the sealing film is obtained by coating the sealing agent described in claim 1 or 2 on the surface of the NdFeB magnet substrate, followed by sealing treatment and heating.
4. The NdFeB magnet according to claim 3, characterized in that: The interface metal is Zn and / or Fe. Preferably, the chemical bond is at least one of Ti-O-Si, Ti-O-Zn, Ti-O-Fe, Si-O-Zn, and Si-O-Fe.
5. The method for preparing a NdFeB magnet according to claim 3 or 4, characterized in that: The method is a galvanizing method or a spraying method; The galvanizing method comprises: (S1) surface cleaning to remove the oxide layer on the surface of the NdFeB magnet substrate; (S2) electroplating: galvanizing the cleaned substrate surface; (S3) passivation treatment: using a brightening liquid and a passivation liquid in sequence to passivate the product after galvanizing in step (S2); (S4) Sealing treatment: using a sealing agent to seal the product after passivation in step (S3), heating it, and obtaining a NdFeB magnet containing a sealing film; The spraying method comprises: (K1) Surface cleaning to remove the oxide layer on the surface of the NdFeB magnet substrate; (K2) Sealing treatment: using a sealing agent to seal the product cleaned in step (K1) and heating it; (K3) Spraying treatment: The product in step (K2) is first preheated and then air-sprayed with paint. After curing, a NdFeB magnet containing a closed film is obtained.
6. The method according to claim 5, characterized in that In step (S3), the light emitting liquid is a 5-20 mL / L nitric acid aqueous solution. Preferably, in step (S3), the passivation solution comprises 10-20 g / L chromium nitrate, 1.5-3 g / L nitrilotriacetic acid, 2-4 g / L oxalic acid, 1.5-2 g / L cobalt sulfate, 0.4-4 g / L γ-aminopropyltriethoxysilane, and 0.5-0.8 g / L sodium tungstate.
7. The method according to claim 5, characterized in that In step (S4), during the sealing treatment, the temperature of the sealing agent is 20-40°C, the time for the product to be treated with the sealing agent is 5-60s, and the concentration of the sealing agent is 8-12wt%. Preferably, in step (S4), the heating temperature is 45-200° C., and the heating time is 10-60 min.
8. The method according to claim 5, characterized in that In step (K3), the preheating temperature is 60-70° C., and the preheating time is 20-150 seconds. Preferably, in step (K3), the curing temperature is 170-190° C., and the curing time is 15-25 min.
9. The method according to claim 5, characterized in that In step (K3), the paint flow rate is 20-30 L / min, the pressure during air spraying is 0.2-0.3 MPa, and the paint viscosity is 10-12 s.
10. Use of the NdFeB magnet containing a closed film as claimed in claim 3 or 4 in galvanizing and spraying for corrosion protection.
Citation Information
Cited By
Silanized surface grain boundary substituted and modified NdFeB magnet and preparation method thereof
CN120727438A
Method for improving surface tension of galvanized neodymium iron boron permanent magnet
CN122011903A